ANALISIS KINERJA KEUANGAN PADA PT INDOSAT OOREDOO HUTCHISON TBK SEBELUM DAN SESUDAH MERGER PERIODE 2020-2024 - Agustinus Farrell Phanali; Ari Agung Nugroho; Darman Saputra (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the differences and assess the impact of the merger on the financial performance of PT Indosat Ooredoo Hutchison Tbk by comparing financial conditions before and after the merger during the 2020–2024 period. The merger represents a strategic move to strengthen the company’s position in Indonesia’s telecommunications industry. This research employs a quantitative approach using secondary data obtained from the company’s annual financial reports. The methods used include descriptive statistical analysis to observe trends in financial ratio changes, and the Wilcoxon Signed Ranks Test to identify significant differences between pre- and post-merger periods. The financial ratios analyzed include the Current Ratio, Quick Ratio, Debt to Assets Ratio, Debt to Equity Ratio, Total Assets Turnover, Fixed Assets Turnover, Return on Assets, Return on Equity, Gross Profit Margin, Net Profit Margin, and Earnings Per Share. The results show that most ratios experienced numerical improvement after the merger. However, the Wilcoxon test results indicate no statistically significant differences. This suggests that the merger has not yet had a significant impact on the company’s overall financial performance in the short term.